Disappearance of Sombath Somphone : time for intervention by ASEAN? - Tan, Kwoh Jack (2013)
The disappearance of prominent Lao acitivist Sombath Somphone is garnering regional and international attention. With the signing of the ASEAN Human Rights Charter it is in the interest of ASEAN countries to engage more actively on the issue.